Production method for reducing casting blank cracks
By optimizing the smelting and continuous casting process and refining the austenite grain size, the problem of cracks on the surface of the casting blank is solved, and the high-temperature plasticity and homogeneity of the casting blank is improved.
Patent Information
- Application Number
- CN202411470187.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively reduce the formation of cracks on the surface of the casting billet, especially when the austenite grain size is large.
By optimizing the chemical composition and mass percentage of the continuous casting billet, and controlling the process parameters of the converter smelting, LF refining, RH refining, slab continuous casting and hot-loading rolling, the austenite grain size in the microstructure of the surface layer of the continuous casting billet is refined, high-temperature plasticity is improved, and cracks are reduced.
It effectively reduces the incidence of cracks on the surface of continuous casting billets, improves the high-temperature plasticity and homogeneity of the casting billets, and avoids the generation of cracks.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a production method for reducing cracks in a casting. Background Art
[0002] Cracks are a major casting defect formed during the continuous casting process of the ingot. This casting defect not only affects the subsequent processing of the ingot and the quality of the final product, but also causes leakage accidents and affects the normal operation of the continuous casting machine.
[0003] The surface cracks of continuous casting billets are mainly formed in the crystallizer, the second cooling section of the continuous casting machine, and during the transportation, lifting, stacking and heating of billets. Among them, the surface cracks of continuous casting billets formed in the crystallizer mainly include longitudinal cracks, transverse cracks, mesh cracks and star-shaped cracks; the surface cracks of continuous casting billets formed in the second cooling section of the continuous casting machine mainly include straightening transverse cracks, mechanical stress cracks and thermal stress cracks; the surface cracks of continuous casting billets formed during the transportation, lifting, stacking and heating of billets mainly include phase change cracks and hot delivery cracks.
[0004] The formation of austenite grain boundary cracks is the fundamental reason for the transverse cracks, network cracks and star-shaped cracks on the surface of the continuous casting billet. In other words, the essence of the transverse cracks, network cracks and star-shaped cracks on the surface of the continuous casting billet is the austenite grain boundary cracks. The high-temperature structure of the billet may be in the γ single-phase region or the γ+α two-phase region, and the γ single-phase region and the γ+α two-phase region are both the temperature ranges for the initiation of austenite grain boundary cracks, so austenite, proeutectoid ferrite and second-phase precipitates are the high-temperature structures of the continuous casting billet. From the microstructure of the surface of the continuous casting billet, the austenite grain boundary cracks on the surface of the continuous casting billet always crack along the coarse original austenite grain boundaries, while the fine original austenite grains can reduce the sensitivity of grain boundary cracks.
[0005] The prior art generally adopts a method of rapid cooling the surface of the continuous casting billet at a certain stage of continuous casting to promote the transformation of the surface of the continuous casting billet from austenite to ferrite + pearlite, so that the carbonitrides of microalloying elements such as Nb, V, and Ti are precipitated in the crystal as much as possible, avoiding the segregation of carbonitrides at the grain boundary to reduce the surface cracks of the continuous casting billet. However, since the grain refinement effect of the above method is not obvious, when the continuous casting billet is reheated in the heating furnace to the two-phase region between Ar1 and Ar3, most of the grain sizes are still above 100μm, and the grain size of this size is not enough to inhibit the generation of surface cracks of hot-delivered casting billets with high crack sensitivity. In addition, high concentrations of microalloying elements will seriously weaken the grain boundary strength. Summary of the invention
[0006] In view of the technical problem that cracks are generated in a continuous casting billet due to a large austenite grain size in a surface microstructure, the present invention provides a production method for reducing cracks in the casting billet, by optimizing the chemical composition and mass percentage of the continuous casting billet, regulating the process parameters of multiple processes such as converter smelting, LF refining, RH refining, slab continuous casting, hot rolling, etc., the austenite grain size in the surface microstructure of the continuous casting billet is refined, the high-temperature plasticity of the continuous casting billet is improved, and the cracks on the surface of the continuous casting billet are reduced.
[0007] The technical solution of the present invention is as follows: A production method for reducing cracks in a casting, comprising the following steps: (1) Pre-desulfurization of molten iron; (2) Converter smelting: Before loading molten steel, the lining temperature of the ladle is controlled to be >800°C; during the converter smelting process, deoxidation and alloying are carried out and fluorite and lime are added. The total amount of fluorite and lime added is 45-55kg / t; the converter adopts top and bottom combined blowing; (3) LF refining: submerged arc heating, deoxidation and alloying, then use lime and aluminum particles to make white slag desulfurization, and then calcium treatment, and control the S content in the molten steel to ≤0.003% before feeding the calcium wire; (4) RH refining: vacuum degree of vacuum dehydrogenation is ≤100Pa, vacuum dehydrogenation time is 10-15min, H content at the end of RH refining is ≤1.5ppm, N content at the end of RH refining is ≤40ppm; titanium wire is fed during RH refining and secondary calcium treatment is performed; (5) Slab continuous casting: full-process protection pouring is adopted, the argon flow rate of the ladle protection pouring sleeve is controlled to be 100-150L / min, the slag layer thickness of the tundish is 60-80mm, and the superheat of the molten steel is 10-20℃; weak cooling is adopted in the front section of the secondary cooling section, and the water output of the front section of the secondary cooling section is 0.40-0.5L / kg, and strong water cooling is adopted in the rear section of the secondary cooling section, and the water output of the rear section of the secondary cooling section is 0.8-1.0L / kg; electromagnetic stirring is used in the fourth to sixth sections of the continuous casting machine fan-shaped section, the frequency of electromagnetic stirring is 9Hz±1Hz, and the coil current of electromagnetic stirring is 500A±10A; (6) Hot rolling: 0.5-1.5 m before the end of solidification of the continuous casting billet, the billet is subjected to large reduction, with a reduction rate of 15% ± 1%. After the hot rolling is completed, a hot rolled billet is obtained. The chemical composition and mass percentage of the continuous casting billet are as follows: C ≤ 0.20%, Si ≤ 0.50%, Mn ≤ 2.0%, P ≤ 0.020%, S ≤ 0.005%, Al: 0.010% - 0.030%, Cu ≤ 0.40%, Nb ≤ 0.40%, Cr ≤ 0.30%, Ti ≤ 0.020%, B ≤ 0.0020%, N ≤ 40ppm, and the rest are Fe and unavoidable impurities, among which 6 ≤ Al / N ≤ 9, 3 ≤ Ti / N ≤ 5, 0.07% ≤ Al + 10 × N + Ti ≤ 0.1%, Cu + 1000 × B ≤ 0.70%.
[0008] Furthermore, in step (1), the final S content of the molten iron is S≤0.0030%. By controlling the final S content of the molten iron, the amount of sulfur-containing brittle inclusions in the molten iron is reduced, which is beneficial to improving the high-temperature plasticity of the continuous casting billet.
[0009] Furthermore, in step (2), the mass ratio of fluorite to lime is 0.2-0.5. One or more deoxidizing agents selected from flux, aluminum deoxidizer, calcium carbide and aluminum particles are added to the molten steel, wherein the flux mainly comprises aluminum oxide and lime, and the mass percentage of aluminum oxide in the flux is 65%-70%, preferably 68%; the aluminum deoxidizer is aluminum manganese iron, and the amount thereof is determined according to the end point oxygen, and the amount of the aluminum deoxidizer is 400-600 kg; the amount of aluminum particles is 0-100 kg, preferably 50-100 kg, and the amount of calcium carbide is 0-80 kg, preferably 40-80 kg.
[0010] Furthermore, in step (2), the final P content of converter smelting is P≤0.015%.
[0011] Furthermore, in step (3), the feeding amount of the calcium treated calcium wire is 0.55-0.75 m / t, and the feeding speed is 115-120 m / min.
[0012] Furthermore, in step (4), the feed amount of the calcium wire for secondary calcium treatment is 0.75-0.85 m / t, and the feed speed is 115-120 m / min.
[0013] Furthermore, in step (4), the feeding amount of the titanium wire is calculated based on the mass percentage of titanium in the molten steel and the weight of the molten steel. The mass percentage of titanium in the molten steel is 0.012%-0.017%, and the feeding speed is 105-115 m / min.
[0014] Furthermore, in step (6), in the microstructure of the hot-rolled ingot, the thickness of the fine grain layer is greater than 5 mm, and the volume ratio of austenite with a grain size of ≥500 μm in the columnar crystal region and the central equiaxed crystal region is less than 10%.
[0015] The beneficial effects of the present invention are: The production method for reducing cracks in cast billets provided by the present invention first utilizes a molten iron pre-desulfurization process to remove S in molten iron; then in a converter smelting process, by controlling the inner lining temperature of the ladle to be greater than 800°C, the temperature drop during steel tapping is reduced, and desired alloy elements are added to the molten steel during deoxidation and alloying, and lime and fluorite are used to make white slag, combined with a top and bottom double blowing process, to fully remove impurity elements such as P and S in the molten steel; and then, LF refining and RH refining are performed in sequence to remove O and S, H and N in the molten steel, thereby further improving the purity of the molten steel.
[0016] In the slab continuous casting process, electromagnetic stirring is used in the fourth to sixth sections of the continuous casting machine sector to reduce the segregation of microalloys and microalloy compounds to grain boundaries in the II brittle temperature zone; strong water cooling is used in the rear section of the second cooling section to promote the rapid precipitation of carbonitrides of microalloying elements such as Nb and Ti inside the grains during the rapid cooling process. Most of the carbonitrides are precipitated in the form of fine dispersion inside the grains, avoiding the large-scale segregation and precipitation of carbon, nitrides and thin-film ferrite on the original austenite grain boundaries, thereby improving the high-temperature plasticity of the surface of the continuous casting slab.
[0017] In the hot rolling process, the continuous casting billet is pressed down 1m before the end of solidification, with a reduction rate of 15%±1%. This can greatly weaken segregation, break up dendrites and proeutectoid film-like ferrite, weld shrinkage cavities to improve density, and greatly improve the uniformity and size of austenite grains after dynamic recrystallization, thereby refining the austenite grains and improving homogeneity. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] Example 1 A production method for reducing cracks in a casting, comprising the following steps: (1) Pre-desulfurization of molten iron: The final sulfur content of molten iron is 0.0025%.
[0020] (2) Converter smelting: Before loading molten steel, the inner lining temperature of the ladle is controlled at 836°C by baking. During the converter smelting process, deoxidation and alloying are carried out, and fluorite and lime are added to make white slag. The total amount of fluorite and lime added is 52 kg / t, and the mass ratio of fluorite to lime is 0.32. The converter adopts top and bottom double blowing to fully dephosphorize, and the final phosphorus content is 0.009%. During the converter smelting process, argon is blown throughout the process, weak stirring is carried out, and the slag surface is slightly turned over without being exposed.
[0021] (3) LF refining: After deoxidation and alloying, heating is carried out under good submerged arc conditions, and white slag is made with lime and aluminum particles for desulfurization and reduction of N addition, and then calcium treatment is carried out. The S content in the molten steel is controlled to be 0.0025% before feeding the calcium wire, the calcium wire feeding amount is 0.6m / t, and the calcium wire feeding speed is 120m / min.
[0022] (4) RH refining: the vacuum degree of vacuum dehydrogenation is ≤88Pa, the time of vacuum dehydrogenation is 13min, the end point H content of RH refining is 1.3ppm, and the end point N content of RH refining is 35ppm; during RH refining, titanium wire is fed, the mass percentage of Ti is controlled to be 0.015%, the feeding speed of titanium wire is 110m / min, and secondary calcium treatment is carried out. The feeding amount of calcium wire for secondary calcium treatment is 0.8m / t, and the feeding speed is 120m / min.
[0023] (5) Slab continuous casting: full-process protective pouring was adopted, the argon flow rate of the ladle protective pouring sleeve was controlled to be 120 L / min, the slag layer thickness of the tundish was 68 mm, and the superheat of the molten steel was 15 °C; weak cooling was adopted in the front section of the secondary cooling section, and the water output of the front section of the secondary cooling section was 0.42 L / kg; strong water cooling was adopted in the rear section of the secondary cooling section, and the water output of the rear section of the secondary cooling section was 0.90 L / kg; electromagnetic stirring rollers were used in the fourth to sixth sections of the continuous casting machine fan section for electromagnetic stirring, the frequency of electromagnetic stirring was 9 Hz, and the coil current of electromagnetic stirring was 500 A.
[0024] (6) Hot rolling: 1 m before the solidification end of the continuous casting billet, the billet was subjected to large reduction, with a reduction rate of 15.2%. After the hot rolling was completed, a hot-rolled billet was obtained. The chemical composition and mass percentage of the continuous casting billet were as follows: C 0.12%, Si 0.23%, Mn 1.60%, P 0.014%, S 0.002%, Al 0.028%, Cu 0.34%, N 35ppm, H 1.3ppm, Nb 0.035%, Ti 0.015%, B: 0.0003%, and the rest were Fe and unavoidable impurities, among which Al / N=8, Ti / N=4.29, Al+10×N+Ti=0.078%, Cu+1000×B=0.64%. In the microstructure of the hot-rolled ingot, the thickness of the fine grain layer is 15 mm, and the volume ratio of austenite with a grain size ≥ 500 μm in the columnar crystal zone and the central equiaxed crystal zone is 2%-3%.
[0025] The crack incidence of the hot rolled ingot obtained in step (6) was tested by visual inspection or the sulfur print inspection method of GB 4236 steel. The main chemical components and mass percentages of the continuous casting ingot and the crack incidence of the hot rolled ingot are shown in Table 1.
[0026] Example 2 A production method for reducing cracks in a casting, comprising the following steps: (1) Pre-desulfurization of molten iron: The final sulfur content of molten iron is 0.0020%.
[0027] (2) Converter smelting: Before loading molten steel, the inner lining temperature of the ladle is controlled at 853°C by baking. During the converter smelting process, deoxidation and alloying are carried out, and fluorite and lime are added to make white slag. The total amount of fluorite and lime added is 53 kg / t, and the mass ratio of fluorite to lime is 0.35. The converter adopts top and bottom double blowing to fully dephosphorize, and the final phosphorus content is 0.010%. During the converter smelting process, argon is blown throughout the process, weak stirring is carried out, and the slag surface is slightly turned over without being exposed.
[0028] (3) LF refining: After deoxidation and alloying, heating is carried out under good submerged arc conditions, and white slag is made with lime and aluminum particles for desulfurization and reduction of N addition, and then calcium treatment is carried out. The S content in the molten steel is controlled to be 0.0020% before feeding the calcium wire, the calcium wire feeding amount is 0.7m / t, and the calcium wire feeding speed is 120m / min.
[0029] (4) RH refining: the vacuum degree of vacuum dehydrogenation is ≤86Pa, the time of vacuum dehydrogenation is 14min, the end point H content of RH refining is 1.1ppm, and the end point N content of RH refining is 38ppm; during RH refining, titanium wire is fed, the mass percentage of Ti is controlled to be 0.016%, the feeding speed of titanium wire is 110m / min, and secondary calcium treatment is carried out. The feeding amount of calcium wire for secondary calcium treatment is 0.8m / t, and the feeding speed is 120m / min.
[0030] (5) Slab continuous casting: full-process protective pouring was adopted, the argon flow rate of the ladle protective pouring sleeve was controlled to be 118 L / min, the slag layer thickness of the tundish was 65 mm, and the superheat of the molten steel was 14 °C; weak cooling was adopted in the front section of the secondary cooling section, and the water output of the front section of the secondary cooling section was 0.43 L / kg; strong water cooling was adopted in the rear section of the secondary cooling section, and the water output of the rear section of the secondary cooling section was 0.95 L / kg; electromagnetic stirring rollers were used in the fourth to sixth sections of the continuous casting machine fan section for electromagnetic stirring, the frequency of electromagnetic stirring was 9 Hz, and the coil current of electromagnetic stirring was 500 A.
[0031] (6) Hot rolling: 1 m before the end of solidification of the continuous casting billet, the billet was subjected to large reduction, with a reduction rate of 15.4%. After the hot rolling was completed, a hot-rolled billet was obtained. The chemical composition and mass percentage of the continuous casting billet were as follows: C 0.16%, Si 0.26%, Mn 1.13%, P 0.015%, S 0.001%, Al 0.027%, Nb 0.028%, Ti: 0.016%, B: 0.0004%, N 38ppm, H 1.1ppm, and the rest were Fe and unavoidable impurities, among which Al / N = 7.11, Ti / N = 4.21, Al+10×N+Ti = 0.081%, and Cu+1000×B = 0.40%. In the microstructure of the hot-rolled ingot, the thickness of the fine grain layer is 16 mm, and the volume ratio of austenite with a grain size ≥ 500 μm in the columnar crystal zone and the central equiaxed crystal zone is 3%-4%.
[0032] The crack incidence of the hot rolled ingot obtained in step (6) was tested by visual inspection or the sulfur print inspection method of GB 4236 steel. The main chemical components and mass percentages of the continuous casting ingot and the crack incidence of the hot rolled ingot are shown in Table 1.
[0033] Comparative Example 1 A method for producing a casting blank comprises the following steps: (1) Pre-desulfurization of molten iron: The final sulfur content of molten iron is 0.0050%.
[0034] (2) Converter smelting: Before loading molten steel, the inner lining temperature of the ladle is controlled at 720°C by baking. During the converter smelting process, deoxidation and alloying are carried out, and fluorite and lime are added to make white slag. The total amount of fluorite and lime added is 38 kg / t, and the mass ratio of fluorite to lime is 0.11. The converter adopts top and bottom double blowing to fully dephosphorize, and the final phosphorus content is 0.014%. During the converter smelting process, argon is blown throughout the process, weak stirring is carried out, and the slag surface is slightly turned over without being exposed.
[0035] (3) LF refining: After deoxidation and alloying, heating is carried out under good submerged arc conditions, and white slag is made with lime and aluminum particles for desulfurization and reduction of N addition, and then calcium treatment is carried out. The S content in the molten steel is controlled to be 0.005% before feeding the calcium wire. The calcium wire feeding amount is 0.3m / t and the feeding speed is 120m / min.
[0036] (4) RH refining: the vacuum degree of vacuum dehydrogenation is ≤200Pa, the time of vacuum dehydrogenation is 13min, the end point H content of RH refining is 2.3ppm, and the end point N content of RH refining is 50ppm; during RH refining, titanium wire is fed, the mass percentage of Ti is controlled to be 0.012%, the feeding speed of titanium wire is 130m / min, and secondary calcium treatment is carried out. The feeding amount of calcium wire for secondary calcium treatment is 0.6m / t, and the feeding speed is 120m / min.
[0037] (5) Slab continuous casting: Full-process protective pouring was adopted, and the argon flow rate of the ladle protective pouring sleeve was controlled to be 103 L / min. The slag layer thickness of the tundish was 40 mm, and the superheat of the molten steel was 32 °C. Weak cooling was adopted in the secondary cooling section, and the water output of the secondary cooling section was 0.39 L / kg. Electromagnetic stirring rollers were used in the fourth to sixth sections of the continuous casting machine sector for electromagnetic stirring. The frequency of electromagnetic stirring was 5 Hz, and the coil current of electromagnetic stirring was 250 A.
[0038] (6) Hot rolling: 1 m before the solidification end of the continuous casting billet, the billet was subjected to large reduction, with a reduction rate of 11.4%. After the hot rolling was completed, a hot-rolled billet was obtained. The chemical composition and mass percentage of the continuous casting billet were as follows: C 0.18%, Si 0.28%, Mn 1.40%, P 0.016%, S 0.006%, Nb 0.030%, Ti: 0.012%, Cu 0.36%, B: 0.0006%, Al 0.022%, N 50ppm, H2.3ppm, and the rest were Fe and unavoidable impurities, among which Al / N=4.4, Ti / N=2.40, Al+10×N+Ti=0.084%, Cu+1000×B=0.96%. In the microstructure of the hot-rolled ingot, the thickness of the fine grain layer is 6 mm, and the volume ratio of austenite with a grain size ≥ 500 μm in the columnar crystal zone and the central equiaxed crystal zone is 18%-20%.
[0039] The crack incidence of the continuous casting slab obtained in step (6) was tested by visual inspection or the sulfur print inspection method of GB 4236 steel. The main chemical components and mass percentages of the continuous casting slab and the crack incidence of the continuous casting slab are shown in Table 1.
[0040] Table 1 Main chemical composition and crack incidence of continuous casting slabs obtained in Examples 1-2 and Comparative Example 1
[0041] Although the present invention has been described in detail by combining the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person skilled in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A production method for reducing cracks in a casting, characterized in that: Including the following processes: (1) Pre-desulfurization of molten iron; (2) Converter smelting: Before loading molten steel, the lining temperature of the ladle is controlled to be >800°C; during the converter smelting process, deoxidation and alloying are carried out and fluorite and lime are added. The total amount of fluorite and lime added is 45-55kg / t; the converter adopts top and bottom combined blowing; (3) LF refining: submerged arc heating, deoxidation and alloying, then use lime and aluminum particles to make white slag desulfurization, and then calcium treatment, and control the S content in the molten steel to ≤0.003% before feeding the calcium wire; (4) RH refining: vacuum degree of vacuum dehydrogenation is ≤100Pa, vacuum dehydrogenation time is 10-15min, H content at the end of RH refining is ≤1.5ppm, N content at the end of RH refining is ≤40ppm; titanium wire is fed during RH refining and secondary calcium treatment is performed; (5) Slab continuous casting: adopt full-process protective pouring, control the argon flow rate of the ladle protective pouring sleeve to 100-150L / min, the slag layer thickness of the tundish to 60-80mm, and the superheat of the molten steel to 10-20℃; The front section of the secondary cooling section adopts weak cooling, and the water output of the front section of the secondary cooling section is 0.40-0.5L / kg. The rear section of the secondary cooling section adopts strong water cooling, and the water output of the rear section of the secondary cooling section is 0.8-1.0L / kg; electromagnetic stirring is used in the fourth to sixth sections of the continuous casting machine fan-shaped section, the frequency of electromagnetic stirring is 9Hz±1Hz, and the coil current of electromagnetic stirring is 500A±10A; (6) Hot rolling: 0.5-1.5 m before the end of solidification of the continuous casting billet, the billet is subjected to large reduction, with a reduction rate of 15% ± 1%. After the hot rolling is completed, a hot rolled billet is obtained. The chemical composition and mass percentage of the continuous casting billet are as follows: C ≤ 0.20%, Si ≤ 0.50%, Mn ≤ 2.0%, P ≤ 0.020%, S ≤ 0.005%, Al: 0.010% - 0.030%, Cu ≤ 0.40%, Nb ≤ 0.40%, Cr ≤ 0.30%, Ti ≤ 0.020%, B ≤ 0.0020%, N ≤ 40ppm, and the rest are Fe and unavoidable impurities, among which 6 ≤ Al / N ≤ 9, 3 ≤ Ti / N ≤ 5, 0.07% ≤ Al + 10 × N + Ti ≤ 0.1%, Cu + 1000 × B ≤ 0.70%.
2. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (1), the final sulfur content of the molten iron is S≤0.0030%.
3. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (2), the mass ratio of fluorite to lime is 0.2-0.
5.
4. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (2), the final P content of converter smelting is P≤0.015%.
5. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (3), the feed amount of calcium treated calcium wire is 0.55-0.75 m / t, and the feed speed is 115-120 m / min.
6. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (4), the feed amount of the calcium wire for secondary calcium treatment is 0.75-0.85 m / t, and the feed speed is 115-120 m / min.
7. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (4), the feeding amount of the titanium wire is calculated based on the mass percentage of titanium in the molten steel and the weight of the molten steel. The mass percentage of titanium in the molten steel is 0.012%-0.017%, and the feeding speed is 105-115 m / min.
8. A production method for reducing cracks in a casting according to claim 1, characterized in that: In step (6), in the microstructure of the hot rolled ingot, the thickness of the fine grain layer is greater than 10 mm, and the volume ratio of austenite with a grain size of ≥500 μm in the columnar crystal region and the central equiaxed crystal region is less than 10%.
Citation Information
Cited By
Continuous casting method for titanium-containing steel
CN120438544A
Control method for preventing saw blade steel continuous casting billet from being broken
CN120843958A